2009
DOI: 10.1186/1742-4682-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a polycystic ovarian syndrome (PCOS) pathway based on the interactions of PCOS-related proteins retrieved from bibliomic data

Abstract: Polycystic ovary syndrome (PCOS) is a complex but frequently occurring endocrine abnormality. PCOS has become one of the leading causes of oligo-ovulatory infertility among premenopausal women. The definition of PCOS remains unclear because of the heterogeneity of this abnormality, but it is associated with insulin resistance, hyperandrogenism, obesity and dyslipidaemia. The main purpose of this study was to identify possible candidate genes involved in PCOS. Several genomic approaches, including linkage analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…41 In addition, some other genes were found to be differentially expressed in relevant tissues of the PCOS patients, including ones encoding for insulin signalling components (IRS-1, pIRS-1Y612, GLUT4), sex hormone-binding globulin (SHBG), adiponectin 45 and inflammatory cytokines (IL-6, IL-18, TNFa). 42,46 Functions of PCOS related genes are summarised in Table 1.…”
Section: The Role For Environment Factors In Pcos and Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…41 In addition, some other genes were found to be differentially expressed in relevant tissues of the PCOS patients, including ones encoding for insulin signalling components (IRS-1, pIRS-1Y612, GLUT4), sex hormone-binding globulin (SHBG), adiponectin 45 and inflammatory cytokines (IL-6, IL-18, TNFa). 42,46 Functions of PCOS related genes are summarised in Table 1.…”
Section: The Role For Environment Factors In Pcos and Nafldmentioning
confidence: 99%
“…44 As a large number of lypoxygenase-oxidised fatty acids become leukotrienes, which are natural chemical substances in the body that promote inflammatory response to damage, an impaired lipoxygenase function can theoretically contribute to the inflammatory condition seen in PCOS. 46 Incidentally, it was shown that the lipoxygenase encoded by ALOX15 augments the resistance to insulin, whereas its inhibition enhances the action of insulin in rat models of insulin resistance and type 2 diabetes. 77 12 ⁄ 15 lipoxigenase deficient mice are resistant to streptozotocin-induced diabetes.…”
Section: Leukotriene Metabolism Related Genes Alox15 Fem1a Fem1bmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies utilized cDNA microarrays in theca cells [9], whole ovaries [10,11], oocytes [12], and cumulus cells [13]. The data from these studies revealed a number of the genes associated with PCOS are primarily involved in the insulin receptor signaling pathway, steroid biosynthesis, and the regulation of gonadotropin secretion [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are three main categories to construct Biomolecular regulatory network : constructing gene regulatory networks through a mathematical model ; building a network through literature mining and integrating multiple data (Friedman et al, 2000;Hwang et al, 2005;Mohamed et al, 2009). Liu Y etc.…”
Section: Discussionmentioning
confidence: 99%